Where Truth Lies - Fallon, Kris (University of California Press, 2020)
"This boldly original book traces the evolution of documentary film and photography as they migrated onto digital platforms during the first decades of the twenty-first century. Kris Fallon examines the emergence of several key media forms—social networking and crowdsourcing, video games and virtual environments, big data and data visualization—and demonstrates the formative influence of political conflict and the documentary film tradition on their evolution and cultural integration. Focusing on particular moments of political rupture, Fallon argues that ideological rifts inspired the adoption and adaptation of newly available technologies to encourage social mobilization and political action, a function performed for much of the previous century by independent documentary film. Positioning documentary film and digital media side by side in the political sphere, Fallon asserts that “truth” now lies in a new set of media forms and discursive practices that implicitly shape the documentation of everything from widespread cultural spectacles like wars and presidential elections to more invisible or isolated phenomena like the Abu Ghraib torture scandal or the “fake news” debates of 2016. “Looking at a unique and intriguing set of ‘hybrid media,’ Fallon convincingly makes a claim about a change in the form of new media, one linking politics, aesthetics, and technology.” ALEXANDRA JUHASZ, Brooklyn College, CUNY “Where Truth Lies does the difficult and much-needed work of unpacking how the documentary impulse is shifting in the digital age, both through the profound influence of digital aesthetics and computational thinking and through the ways traditional documentary is infusing digital expression.” JENNIFER MALKOWSKI, author of Dying in Full Detail: Mortality and Digital Documentary KRIS FALLON is Assistant Professor of Cinema and Digital Media at the University of California, Davis."